Introduction. (30th May 2016) - Eriksen, Annelin; MacCarthy, Michelle
Abstract : Taking as a starting point the 1981 volume Gender and Kinship: Essays Towards a Unified Analysis, we here outline our approach to bring together analyses of gender and Christianity in Melanesia. We argue that studies of gender and Christianity must go beyond studies of men's and women's respective activities or roles in the church, and rather interrogate the ways in which Christian morality and social life become gendered in various ways.